Prevalence of severe Plasmodium knowlesi infection and risk factors related to severe complications compared with non-severe P. knowlesi and severe P. falciparum malaria: a systematic review and meta-analysis - Manas Kotepui; Kwuntida Uthaisar Kotepui; Giovanni D. Milanez; Frederick R. Masangkay (BMC, 2020)
Abstract Background Plasmodium knowlesi is a potential cause of severe and fatal malaria, but comprehensive studies of its pooled prevalence and risk factors are lacking. This study aimed to explore the prevalence and risk factors related to severe P. knowlesi infection. Methods A systematic review was conducted by retrieving all published articles on severe P. knowlesi available in Web of Science (ISI), Scopus, and PubMed (MEDLINE). Titles, abstracts, and full-text articles were screened, and any irrelevant studies were excluded. The random-effects model was used to compute the pooled prevalence estimate of severe P. knowlesi infection by a metaprop command provided in STATA software. Differences in demographic characteristics, clinical characteristics, and laboratory data were analysed using Review Manager Version 5.3 software for patients in the following groups: 1) patients with severe and non-severe P. knowlesi infection and 2) patients with severe P. knowlesi and severe P. falciparum infection. Results Out of the 2382 studies retrieved from the three databases, seven studies with a total enrolment of 1124 patients with P. knowlesi infections were eligible to be included in this systematic review and meta-analysis. The pooled prevalence estimate of severe P. knowlesi infection was 19% (95% CI: 11-27%, I 2 = 93.7%). Severe acute kidney injuries (AKI) (77 cases, 45.6%), jaundice (71 cases, 42%), and hyperparasitaemia (55 cases, 32.5%) were the common clinical manifestations found among patients with severe complications. In comparison to non-severe P. knowlesi infections, patients with severe P. knowlesi infections had significantly higher age, leucocyte count, and parasitaemia levels (P < 0.05). In comparison to patients with severe P. falciparum infections, patients with severe P. knowlesi infections had significantly higher age, neutrophil count, and creatinine levels (P < 0.05). Conclusions This systematic review and meta-analysis demonstrated a high proportion of severe P. knowlesi infections. Patients with severe P. knowlesi infections had higher age, leucocyte count, and parasitaemia levels than those with non-severe P. knowlesi infections. In addition, patients with severe P. knowlesi infections had higher age, neutrophil count, and creatinine levels than those with severe P. falciparum infections.